Ultrasound shear-wave elasticity and magnetic resonance diffusion coefficient show strong inverse correlation in small fibroadenomas - TÜRELİ, DERYA (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: Stiffness of breast lesions helps distinguish malignant from benign solid masses. Stiffness can he quantitatively measured by magnetic resonance and ultrasound imaging using apparent diffusion coefficient (ADC) and shear-wave elastography (SWE) techniques, respectively. This study aims to analyze correlations between SWE and ADC in biopsy-proven small fibroadenomas. Patients and Methods: Shear-wave elastography and ADC measurements of 50 fibroadenomas were evaluated retrospectively. Mean patient age was 41 +/- 13 years (range 27-63). All lesions had maximum diameters of <= 20 millimeters. Correlations between intralesional ADC, lesion-parenchyma ADC ratio, intralesional SWE, SWE heterogeneity index and lesion volume were analyzed. Results: Mean values of lesions were as follows: ADC=1.71 +/- 0.22 x10-3mm2/s, ADC ratio=1.04 +/- 0.09, maximum SWE=73.4 +/- 28.8 kPa, minimum SWE=43.9 +/- 21.8 kPa and SWE heterogeneity index =29.4 +/- 12.7 kPa. There was a strong inverse correlation between fibroadenoma ADC and SWE values (rho - 0.746, p <0.01). Significant correlations were also found between fihroadenoma volume and ADC (rho = - 0.525, p <0.05) and SWE (rho = 0.840, p <0.01). Conclusion: Apparent diffusion coefficient and SWE values show strong inverse correlation in small fibroadenomas. If proven threshold values for lesion characterization are revealed, ultrasonographic SWE and diffusion-weighted MRI have potential to be used interchangeably.
Keywords: Apparent diffusion coefficient; Fihroadenoma of breast; Magnetic resonance imaging; Ultrasound shear-wave elastography; BREAST; ELASTOGRAPHY